The Relationship between Transformational Leadership and the Effectiveness of Educational Institutions in the Tawarawadee Network under the Secondary Educational Service Area Office Prachinburi-Nakhon Nayok - พิมพ์ทอง นัฐพล; ขวัญบุญจันทร์ สุปราณี; รักษนคร กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1. study the level of transformational leadership among school administrators; 2. study the level of school effectiveness; and 3. study the relationship between transformational leadership and school effectiveness. A sample of 167 people was selected using the Krejcie and Morgan table, employing stratified sampling and simple random sampling via lottery. The research instrument was a questionnaire. Statistical analyses included mean, standard deviation, and Pearson Product-moment Correlation Coefficient. The research findings showed that: 1. The transformational leadership of school administrators in the Thawarawadi network schools under the Prachinburi-Nakhon Nayok Secondary Educational Service Area Office was generally at the highest level of opinion. 2. The overall school effectiveness of the Thawarawadi network schools under the Prachinburi-Nakhon Nayok Secondary Educational Service Area Office was also generally at the highest level of opinion. 3. The relationship between transformational leadership and school effectiveness was also examined. The Thawarawadi network group, under the Prachinburi-Nakhon Nayok Secondary Educational Service Area Office, was found to have an overall high level of effectiveness (rxty = 0.944) with statistical significance at the .01 level for the effectiveness of schools under the Prachinburi-Nakhon Nayok Secondary Educational Service Area Office.